So you want to be president? - St. George, Judith (New York Philomel Books, 2000)
Presents an assortment of facts about the qualifications and characteristics of U. S. presidents, from George Washington to Bill Clinton
D., unk., 2005
Keywords: Presidents -- United States -- Miscellanea -- Juvenile literature